Distinctive properties of the hyaluronan-binding domain in the lymphatic endothelial receptor Lyve-1 and their implications for receptor function. - Banerji, S; Hide, B; James, JR; Noble, M; Jackson, D (2010)
The lymphatic endothelial hyaluronan (HA) receptor Lyve-1 is a member of the Link protein superfamily most similar to the leukocyte HA receptor CD44. However, the structure of Lyve-1 and the nature of its interaction with ligand are obscure. Here we present new evidence that Lyve-1 is functionally distinct from CD44. Using truncation mutagenesis we confirm that Lyve-1 in common with CD44 contains an extended HA-binding unit, comprising elements flanking the N and C termini of the consensus lectin-like Link module, bridged by a third conserved disulfide linkage that is critical for HA binding. In addition, we identify six essential residues Tyr-87, Ile-97, Arg-99, Asn-103, Lys-105, and Lys-108 that define a compact HA-binding surface on Lyve-1, encompassing the epitope for an adhesion-blocking monoclonal antibody 3A, in an analogous position to the HA-binding surface in CD44. The overtly electrostatic character of HA binding in Lyve-1 and its sensitivity to ionic strength (IC(50) of 150 mm NaCl) contrast markedly with CD44 (IC(50) > 2 m NaCl) in which HA binding is mediated by hydrogen bonding and hydrophobic interactions. In addition, unlike the extended Link module in CD44, which binds HA efficiently when expressed as a soluble monomer (K(d) = 65.7 mum), that of Lyve-1 requires artificial dimerization, although the full ectodomain is active as a monomer (K(d) = 35.6 mum). Finally, full-length Lyve-1 did not form stable dimers in binding-competent 293T transfectants when assessed using bioluminescent resonance energy transfer. These results reveal that elements additional to the extended Link module are required to stabilize HA binding in Lyve-1 and indicate important structural and functional differences with CD44.